Time series analysis of Nevirapine syrup consumption in prevention of mother-tochild transmission and optimal supply chain model in Oshana region, Namibia - Emmanuel Magesa; Honore M. Kabwebwe; Penehafo Angula (AOSIS, 2020)
HIV/AIDS continue to be serious communicable disease whose impact on public health in Namibia is massive. It is estimated that the prevalence rate of HIV in Namibia is 17.2%, ranking the country as the fifth highest in sub-Saharan Africa (SSA). Some improvement in reducing the number of cases of HIV/AIDS has been made in the country, but the sporadic shortage of medicines continues to slow down government efforts to foster the emergence of an HIVfree generation of Namibians. Develop and demonstrate a mathematical supply-chain model, which can establish parameters to prevent stock-outs of NVP suspension. The study adopted retrospective approach to acquire data from 2012-2016. Gamma supply chain model was developed as the optimal model for NVP syrup and forecasted consumption for 2017-2018 was determined. It is a recommendation of this study that new guidelines for implementation of optimal supply-chain models at the regional medical store, health centers and clinics be implemented for Nevirapine syrup.